Variação espacial dos múltiplos caminhos que conectam ambiente e biodiversidade - Pereira, Elisa Barreto (2020)
Biodiversity is not evenly distributed around the globe, and a major challenge in ecology and evolution is to unravel the processes that generate and maintain spatial patterns of diversity. Decades of research on the subject indicates that current patterns of biodiversity result from a complex network between multiple factors acting over time and space. In this thesis, we explore how the relationships that make up part of this network vary across geographical space on a global scale and propose a spatiotemporal series of paleoclimate, which has the potential to elucidate the spatial variation of biodiversity. We begin by developing a spatially explicit path analysis to explore the spatial non-stationarity of the relationships between current and past environmental conditions with species richness and phylogenetic diversity of terrestrial mammals (first chapter). We show that environmental conditions relate differently to each dimension of diversity, explaining why species richness is not always an indicative of the amount of phylogenetic diversity in a community. Then, we employ the same methodological approach to revisit traditional ecological theories of how climate and productivity influence the richness of terrestrial tetrapods (second chapter). We show that temperature and precipitation have direct and indirect effects, via productivity, on species richness and we explicitly map where each environmental condition is most determinant for the richness of each taxonomic group. Based on the recognition that we still know little about islands biogeography of terrestrial mammals, we generated a global database of island mammals and estimated how richness and endemism are related to the physical and environmental characteristics of the islands, while accommodating non-stationarity between biogeographic regions (third chapter). We show that island’s area and isolation are among the strongest drivers of mammalian biodiversity, while environmental effects varied with taxonomic group, biogeographic region and measure of diversity. The results from the first three chapters point to the great importance of current and past climate for the generation and maintenance of spatial patterns of biodiversity. Therefore, we propose a global spatiotemporal series of the climate during the last 5 million years (Pliocene-Pleistocene), which holds the potential to advance our understanding of the strong diversity-climate relationship (fourth chapter).